Taxonomic notes on Physoderinae (Heteroptera: Reduviidae) from China - Cao, Liangming; Tomokuni, Masaaki; Cai, Wanzhi (Zootaxa, 2011)
Species of the small reduviid subfamily Physoderinae from China are reviewed and two species are recognized in the genus Physoderes Westwood. Physoderes esakii is formally described for Esaki’s (1931) Epirodera latithorax nom. nud. based on his unique specimen kept in the Entomological Laboratory of Kyushu University. Physoderes impexa Distant, 1903 is recorded for the first time from China with a detailed redescription. A key for these two species is also given.